Allelopathic activity of the picocyanobacterium Synechococcus sp. under varied light, temperature, and salinity conditions. Issue 1 (8th February 2016) - Śliwińska‐Wilczewska, Sylwia; Pniewski, Filip; Latała, Adam
Abstract : The impact of environmental factors and mode of action of allelopathic compounds produced by picocyanobacteria on microalgae remains unknown. Therefore, it is essential to characterize allelopathic interactions under different experimental conditions. In this study, the influence of allelopathic activity on the diatom Navicula perminuta was investigated by the addition of cell‐free filtrate of picocyanobacterium Synechococcus sp. cultures grown under different light, temperature, and salinity conditions. Temperature affected the most the donor cyanobacterium by increasing its allelopathic activity. The highest decline in growth, fluorescence parameter F v / F m and maximal photosynthesis P m were observed after the addition of cell‐free filtrate obtained from Synechococcus sp. grown at 190 μmol photons · m −2  · s −1, 25°C and 8 PSU. These studies indicate for the first time that the picocyanobacterium Synechococcus sp. affect coexisting diatom N. perminuta negatively. It was examined that the Synechococcus sp. reveals allelopathic activity on the photosynthesis and chlorophyll fluorescence, which results in the inhibition of growth of analyzed microalgae. These findings indicate that the production of allelopathic substances by picocyanobacterium is regulated by the availability of environmental factors such as light, temperature, and salinity. Moreover, these results demonstrated that variation in light intensity, water temperature, and salinity should be considered when estimating the potential effects of cyanobacterial allelopathy in aquatic environments.